2021
DOI: 10.18037/ausbd.959251
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Inflation in Emerging Markets and Developing Countries: A Literature Review

Abstract: A vast literature exists on the determinants of inflation in developed countries whereas the one in emerging markets and developing countries has gained attention at the beginning of 1990s. In this respect, the current paper overviews the empirical studies in order to provide underlying knowledge and common facts on this topic that are valuable for further research and policymakers. The patterns emerge from the results of the existing literature can be summarized as follows. First, inflation is mainly a moneta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
0
0
Order By: Relevance
“…Under inefficient markets, the price would be inflexible due to, for example, a lack of competition and information, [41,43,50]. This finding is consistent with previous work, especially for emerging markets and developing countries [63][64][65].…”
Section: Empirical Results and Discussionsupporting
confidence: 86%
“…Under inefficient markets, the price would be inflexible due to, for example, a lack of competition and information, [41,43,50]. This finding is consistent with previous work, especially for emerging markets and developing countries [63][64][65].…”
Section: Empirical Results and Discussionsupporting
confidence: 86%
“…Taking into account empirical findings of the studies which focused on the inflation determinants (particularly [42], [50] and [3]) as a convenient econometric approach we constructed an Autoregressive Distributed Lag (ARDL) model applicable for both non-stationary time series as well as for times series with mixed order of integration [58, p. 79], given the fact that real economic data do not often express stationary behaviour. In case of selected variables for Serbia, most time series expressed nonstationary nature in the observed period (from Q1 2009 to Q4 2021), which was the main reason we opted for the ARDL model, which could have provided realistic and efficient estimates.…”
Section: Results and Discussion: Partmentioning
confidence: 99%
“…The corporate sector inflation expectations for one year do not impact the actual inflation in the long run. By running ARDL Error Correction Regression, we obtained Error Correction Term (ECT t-1 ), which indicates the speed of adjustment from short run to long run equilibrium [5,3,984]. High estimated coefficient of the ECT t-1 , which is both negative and statistically significant (at 1% significance level), revealed that potential disequilibrium in the ARDL model can be adjusted in the long run with higher speed in case of any type of shock in the explanatory variables [10, p. 147].…”
Section: Relationship Between Variables In the Long Runmentioning
confidence: 99%